Impact of Weaning and Maternal Immune Activation on the Metabolism of Pigs - Southey, Bruce R.; Bolt, Courtni R.; Rymut, Haley E.; Keever, Marissa R.; Ulanov, Alexander V.; Li, Zhong; Rund, Laurie A.; Johnson, Rodney W.; Rodriguez-Zas, Sandra L. (Frontiers in Molecular Biosciences, 2021)
Weaning wields environmental, social and nutritional stresses that are detectable in the blood metabolite levels of the offspring. Prenatal stress in the form of maternal immune activation (MIA) in response to infection, which is associated with health and behavior disorders, also elicits prolonged changes in blood and brain cytokine and metabolite levels in the offspring. The goal of this study is to investigate the effects of weaning and MIA on the offspring liver function to advance the understanding of the impact of stressors on peripheral and central nervous systems, physiology and health. Gas chromatography mass spectrometry analysis was used to compare the level of hepatic metabolites from 22-day-old pigs (n=48) evenly distributed among weaning (nursed or weaned), viral MIA exposure (yes or no), and sexes. Weaning effects were detected on 38 metabolites at P-value < 0.05 (28 metabolites at FDR P-value < 0.05), and sex-dependent MIA effects were detected on 11 metabolites. Multiple intermediate and final products of the enriched (FDR P-value < 0.05) glycolysis and gluconeogensesis and pentose phosphate pathways were over-abundant in nursed relative to weaned pigs. The enriched pathways confirm the impact of weaning on hepatic metabolic shift, oxidative stress, and inflammation. Higher levels of the glucogenic amino acid histidine in pigs exposed to MIA relative to controls suggesting that the role of this metabolite in modulating inflammation may supersede the role of this amino acid as energy source. The lower levels of cholesterol detected in MIA pigs are consistent with hypocholesterolemia profiles detected in individuals with MIA-related behavior disorders. Our findings underline the impact of weaning and MIA stressors on hepatic metabolites that can influence peripheral and central nervous system metabolic products associated with health and behavior disorders.